Analisa Susut Teknis Pada Transformator Distribusi Di Wilayah Kerja PT. PLN (Persero) ULP Bawean - Muhammad Azrul Gunawan; Hadi Tasmono (Jurnal Universal Technic, 2023)
Along with the development of the times, the need for electricity is very necessary. Electrical energy is one of the energy that is needed in using equipment that is related to electrical energy such as household, office and commercial industrial equipment that requires electrical energy. Bawean Island is one of the islands that requires a large amount of electricity due to the growing development of these sectors. With the rapid development of large-scale developments, the need for electricity needs to be increased in order to meet people's demands related to electricity needs. Technical losses are losses that occur for technical reasons where energy is reduced by turning into heat or heat energy. Basically technical losses occur based on energy losses in components caused by errors in the components themselves. Technical losses that occur in distribution transformers are common. In principle, losses always occur because efficiency cannot be 100%. Energy is lost along with distribution from upstream to downstream of distribution transformers. Based on the formulation of the problem taken, the researchers calculated losses at neutral currents, copper losses, total losses, output power and total losses in the form of prices. From the results of the conclusions above, it can be seen that the greater the current in the neutral of the transformer, the more losses that occur in the transformer.